Basic barriers to publishing research in High-Impact Journals - Purwanto, Agus (International Journal of Social and Management Studies, 2021)
The purpose of this research is to identify and investigate and explore barriers to students and lecturers in publishing on High-Impact Journals. This research uses qualitative methods, namely explorative case studies. Primary data collection using semi-structured interviews with respondents as many as 12 students and lecturers in Jakarta who were selected and determined using purposive sampling method. The results of this study indicate that the respondents are students and lecturers has a positive awareness and interest in publishing his articles on High-Impact Journals with several main objectives, namely:to meet the graduation requirements, so that the articles are cited by other writers, to increase competence, and to improve one's reputation. HoweverLikewise, student and lecturer respondents also had some barriers to doing publications in reputable international journals such as limited funds, limitationstime, difficulty finding references, relatively long publication processing time, limitations English language skills, limited ability to use software tools for paper examinations such as similiarity tests and grammar tests as well as the limited destinations of the High-Impact Journals that will be the places to publishthe article. The limitation of this study is that the sample size is still small, namely only five people and research subjects are only students and lecturers in Jakarta and the results are not necessarily the same if the research is carried out on students and lecturers in other places. This research can be a reference for further similar research at different levels of education in another place. For further research, it can be developed with quantitative methods in numbersa larger sample and a wider area for example across countries.